A Proposed discharge dispensation for consumer debtors in Tanzania - Maghembe, Ngwaru Jumanne (University of Pretoria, 2013)
The Tanzanian private sector is growing, partly due to the state’s efforts to conform to the global economy. As the economy expands and the National Microfinance Policy of 2001 is realised, more and more credit has been made available to consumers. As a direct consequence of the increase of credit, the number of over- indebted consumers in Tanzania is on the rise. The current debt relief system is regulated by the Tanzanian Bankruptcy Act no. 9 of 1930, a piece of colonial legislation. Unfortunately this law is ineffective, costly and outdated. Some of the problems identified in this study with this debt relief regime include the lack of a cost- effective alternative to bankruptcy and its total reliance on the judiciary, an institution that is itself overburdened and requires reform. The purpose of this study is to make recommendations for the reform of the current debt relief system and propose a debt relief dispensation for consumer debtors in Tanzania that will efficiently cure over- indebtedness. A wide comparative investigation was undertaken in this study of selected common law, civil and mixed legal systems that have substantial experience with the boom in over-indebted consumers now facing Tanzania. A number of solutions were borrowed from these systems that may potentially solve Tanzania’s debt relief problem. One of the main findings of this thesis is that, over time, developed jurisdictions that rely on credit in the private sector appear to be converging on the same type of procedures and moderate philosophies for consumer debt relief. These include less judicial supervision for debt relief procedures, less freedom of choice for over-indebted consumers when it comes to the type of procedures available, and mandatory surplus income repayments for debtors who can afford it. In order to address the problems of the Tanzanian debt relief system, this thesis proposes a complete overhaul of the administration of debt relief procedures in Tanzania and the introduction of a combined alternative to bankruptcy that consists of three joint procedures. A number of amendments are also proposed for the Bankruptcy Act no.9 of 1930. This thesis states the status of legal developments as they were in the selected jurisdictions on 31 December 2012.
Keywords: Bankruptcy Act; Current debt relief system; Tanzania